The role of SK3 in progesterone-induced inhibition of human fallopian tubal contraction - Duo Zhang; Qian Zhu; Wei Xia; Chenfeng Zhu; Xiaoya Zhao; Yiqin Zhang; Chuqing He; Sifan Ji; Xiaocui Li; Jian Zhang (BMC, 2022)
Abstract Background Normal motor activity of the fallopian tube is critical for human reproduction, and abnormal tubal activity may lead to ectopic pregnancy (EP) or infertility. Progesterone has an inhibitory effect on tubal contraction; however, the underlying mechanisms remain unclear. Small-conductance calcium-activated K+ channel 3 (SK3) is abundantly expressed in platelet-derived growth factor receptor α positive (PDGFRα+) cells and was reported to be important for the relaxation of smooth muscle. The present study aims to explore the expression of SK3 in the human fallopian tube and its role in progesterone-induced inhibition of tubal contraction. Methods We collected specimens of fallopian tubes from patients treated by salpingectomy for EP (EP group) and other benign gynecological diseases (Non-EP group). The expression of SK3 was detected by quantitative real-time polymerase chain reaction, western blot, immunocytochemistry, and immunohistochemistry analyses. Isometric tension experiments were performed to investigate the role of SK3 in progesterone-induced inhibition of tubal contraction. Results The baseline amplitude and frequency of human fallopian tube contraction were both statistically lower in the EP group compared with the non-EP group. The expression levels of SK3 in different portions of fallopian tubes from the non-EP group were significantly higher than in those from the EP group. Progesterone had an inhibitory effect on tubal contraction, mainly on the amplitude, in both groups, and SK3 as well as other calcium-activated K+ channels may be involved. SK3-expressing PDGFRα (+) cells were detected in the human fallopian tube. Conclusions The expression of SK3 is lower in the EP group, and SK3 is involved in the progesterone-induced inhibition of human fallopian tube contraction.